An anti Si/Zr-poisoning strategy of Al grain refinement by the evolving effect of doped complex. (1st May 2023) - Li, Daoxiu; Yan, Xirui; Fan, Yong; Liu, Guiliang; Nie, Jinfeng; Liu, Xiangfa; Liu, Sida
Abstract: The issue of how to avoid the poisoning phenomenon of α-Al grain refinement caused by special elements (such as Si and Zr) has always been the focus of research attention. In this work, the anti Si/Zr-poisoning of α-Al grain refinement was achieved by the evolving effect of a doped TCB complex, which is constituted by B-doped TiC (B-TiC) and C-doped TiB2 (C-TiB2 ). The results indicate that B-TiC in the TCB complex can release Ti atoms in Al melts, and the unique C-TiB2 particles have a reproduction subsequently. The released Ti atoms by B-TiC during the evolution process act as the solute, limiting the grain growth and assisting in the refinement of the α-Al grains. Furthermore, the density functional theory calculations show that the C atoms in the interior of C-TiB2 tend to enhance the adhesion energy of the C-TiB2 /Al interface, improving the nucleation potency for α-Al on C-TiB2 in the Al-Si alloys or Zr-containing Al alloys. The average grain sizes of Al-7Si-0.4Mg and Al-5Cu-0.15Zr with inoculated TCB complex can be refined to 84 ± 7 μm and 63 ± 4 μm from 784 ± 58 μm and 402 ± 32 μm, respectively. Thus, the anti Si/Zr-poisoning of Al grain refinement is synergistically realized based on the dynamically evolving TCB complex. These findings provide a new direction for the grain refinement of the Al-Si alloys or Zr-containing Al alloys, as well as guidance on further research and development of grain refiners. Graphical abstract: Image, graphical abstract